2020
DOI: 10.3389/fimmu.2020.00113
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin of the P2X7 C-ter Region: Capture of an Ancient Ballast Domain by a P2X4-Like Gene in Ancient Jawed Vertebrates

Abstract: P2X purinergic receptors are extracellular ATP-gated ion channel receptors present on the cell plasma membrane. P2X receptors have been found in Metazoa, fungi, amoebas, and in plants. In mammals, P2X7 is expressed by a large number of cell types and is involved in inflammation and immunity. Remarkably, P2X7 does not desensitize as other P2X do, a feature linked to a "C-cysteine anchor" intra-cytoplasmic motif encoded by exon 11. Another specific feature of P2X7 is its C-terminal cytoplasmic ballast domain (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Both genes are believed to be derived from successive gene duplications (Dubyak, 2007;Hou and Cao, 2016). Indeed, a recent report suggests that P2X7 was probably formed in lower vertebrates through the fusion of a P2X4-like gene with a Zn-coordinating cysteine-based domain (ZCD) coding exon (Rump et al, 2020). While heteromerisation of P2X7 and P2X4 in vivo is still controversial, both genes are found to be widely coexpressed (Guo et al, 2007;Kaczmarek-Hajek et al, 2012) and colocalize to act in concert in the regulation of the same physio-pathological functions (Kopp et al, 2019).…”
Section: Topology Of the P2x7 Receptormentioning
confidence: 99%
“…Both genes are believed to be derived from successive gene duplications (Dubyak, 2007;Hou and Cao, 2016). Indeed, a recent report suggests that P2X7 was probably formed in lower vertebrates through the fusion of a P2X4-like gene with a Zn-coordinating cysteine-based domain (ZCD) coding exon (Rump et al, 2020). While heteromerisation of P2X7 and P2X4 in vivo is still controversial, both genes are found to be widely coexpressed (Guo et al, 2007;Kaczmarek-Hajek et al, 2012) and colocalize to act in concert in the regulation of the same physio-pathological functions (Kopp et al, 2019).…”
Section: Topology Of the P2x7 Receptormentioning
confidence: 99%
“…The authors reported the presence of a C-cys anchor domain that, if palmitoylated, causes the typical non-desensitizing current associated with P2X7. Based on this molecular structure, a following study proposed that the P2X7 C terminal domain was acquired by genomic rearrangement from a P2X4-like gene in ancient jawed vertebrates generating the actual mammalian P2X7 [ 17 ]. Therefore, it is not completely surprising that some P2X7 splice variants, which function as a channel but not as macropore have been conserved through evolution [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…P2X7R activated macropore opening was also shown to enhance the intracellular uptake of drugs including chemotherapeutics such as doxorubicin 17 and was therefore proposed as tumor cell-specific drug delivery system 18,19 . The structure of P2X7R C terminal was recently reported 20 and it was speculated that this region was acquired by genomic rearrangement from a P2X4R like-gene in ancient jawed vertebrates generating the actual mammalian P2X7R 21 . It is therefore not surprising that certain species such as humans still express functional P2X7R splice variants missing the C terminal domain such as P2X7RB, an isoform unable to form the macropore, and thus without cytotoxic activity, but still endowed with ion channel properties 22,23 .…”
Section: Introductionmentioning
confidence: 99%